The role of offensive and creative priming videos in enhancing youth football players’ performance during small-sided games - Coutinho, Diogo; Gonçalves, Bruno; Santos, Sara; Olthof, Sigrid; Lengua, Rafael Ballester; Roca, André; Travassos, Bruno (Frontiers in Psychology, 2025)
IntroductionThis study examined the effects of video-based priming interventions on youth football players’ performance prior to playing small-sided games (SSG).MethodsTwenty-four U14 players (age: 13.8 ± 0.4 years, football experience of 7.5 ± 2.3 years) participated in three conditions: (i) CONTROL (no priming), (ii) OFFENSIVE priming (a 4-minute video on progressive possession style leading to goals), and (iii) CREATIVE priming (a 4-minute video emphasizing innovative passes, dribbles, and shots). Tactical and physical performance were assessed using GPS devices, individual tactical performance using the Game Performance Evaluation Tool (GPET), and performance creativity using the CREATIVE Behavior Assessment in Team Sports (CBATS). Data were compared using the non-parametric Friedman ANOVA test.ResultsThe OFFENSIVE condition demonstrated reduced variability in distances to teammates (X2 = 7.00, p = 0.030), and increased overall external load compared to the CONTROL condition. Superior decision-making (X2 = 18.6, p < 0.001) and execution (X2 = 13.2, p = 0.001) in passing actions compared to both the control and creative conditions were observed. The CREATIVE condition promoted increased spatial exploration (X2 = 6.10, p = 0.047), and more frequent shooting attempts (X2 = 7.05, p = 0.029) compared to the CONTROL and OFFENSIVE conditions, and greater variability in distances to opponents compared to the CONTROL condition (X2 = 9.75, p = 0.008).DiscussionThese findings demonstrate that video-based priming can influence tactical, technical, and creative behaviors in SSG. Coaches can leverage offensive priming to improve structured passing and positioning, while creative priming may inspire exploratory movements and innovative shooting attempts.